THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN STRENGTHENING STUDENTS' SELF-CONTROL - Citra Puspita Maulida; Kasuwi Saiban; Umi Salamah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
Seeing the current phenomenon, various problems often arise due to a person's lack of self-control. In the process of strengthening students' self-control, teachers have an important role, especially Islamic Religious Education teachers. The purpose of this study is to describe the role of Islamic Religious Education teachers in strengthening self-control aspects of behavioral control, cognitive control, and decisional control of students. This study uses a qualitative approach with a descriptive research type. Data collection: interviews, observation, and documentation. Data checking uses triangulation, the